Migraine: a brain state amenable to therapy. Issue 1 (6th December 2019) - Eller, Michael; Goadsby, Peter J
Summary: Migraine affects over a billion people worldwide in any year and is the second most common cause of years lost due to disability. Not "just a headache", morbidity washes though society and carries a substantial economic and social cost. Understanding of migraine pathophysiology has progressed significantly. Animal models and functional neuroimaging have yielded significant insight into brain structures that mediate migraine symptoms. The role of small peptides as neurotransmitters within this network has been elucidated, allowing the generation of novel therapeutic approaches that have been validated by randomised placebo‐controlled trials. Migraine is underdiagnosed and undertreated. Treatment of migraine should be proactive. An acute and, when indicated, preventive strategy should be formulated with the patient. Comorbid medication overuse must be supportively managed. Migraine‐specific medications are making their way from bench to bedside. They promise an improved safety profile and ease of use in comparison to older, repurposed medications. Devices promise a non‐drug alternative should patients prefer. The migraine understanding and treatment landscape is changing rapidly.